El E-learning durante la pandemia en los estudiantes de cuarto año paralelo “A” de Educación General Básica de la Unidad Educativa “Liceo Policial Chimborazo” de la ciudad de Riobamba año lectivo 2019 – 2020 - Pinanjota Muñoz, María Fernanda (2021)
The research topic raised from an existing need in Unidad Educativa “Liceo Policial Chimborazo,” in children of fourth-year GBE, to provide a positive contribution to the educational community with active methodologies for virtuality and its main objective is to analyze the impact of E-learning during the pandemic in children of fourth grade “A” GBE in Unidad Educativa “Liceo Policial Chimborazo,” city of Riobamba, the school year 2019 - 2020. It worked with a population of 35 students and four teachers in charge of the fourth year; the non-experimental design investigation was carried out because the variables were not manipulated deliberately. To obtain the results, it used a questionnaire as a technique and a survey as an instrument. To conclude, the students do not have technological devices, no good internet network to access virtual classes. Therefore, they do not attend classes regularly. In addition, teachers are not satisfied with technology use in the educational practice, and they use their methodology for class development. It recommends that teachers must know and apply the didactic methodologies so they facilitate the teaching - learning process by allowing students to build their knowledge.